Pengaruh Media Permainan Dakon Berbasis Etnomatematika terhadap Hasil Belajar Operasi Hitung Bilangan Cacah - Meliasari, Wa Ode; Wardana, Mahardika Darmawan Kusuma (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
The research entitled The Effect of Ethnomathematics-Based Dakon Game Media on Learning Outcomes of Counting Whole Number Operations. This study aims to determine the effect of ethnomathematics-based dakon game media on learning outcomes of counting operations on whole numbers of first grade students at SDN Candinegoro. This study uses experimental quantitative research, the design used is Pre-Experimental type One Group Pretest-Posttest Design. The instrument used in this study was the Pretest-Posttest result test. Based on the results of the research conducted, it is known that the calculation results of the t-test are the tcount value of 7.04 with a significant ttable of 5% db=21–1=20 ttable of 1.72472, then the value of tcount> ttable is 7.04> 1.72472 ( H1 is accepted and H0 is rejected), it can be concluded that there is an influence of ethnomathematics-based dakon game media on the learning outcomes of counting operations on whole numbers for the first grade students of SDN Candinegoro.